Usual interstitial pneumonia - secondary vs idiopathic pulmonary fibrosis - Sharma, Divyendu; Agrawal, Rajesh; Agarwal, Rajat; Kumar, Amit; Gupta, Utkarsh (International Journal of Research in Medical Sciences, 2019)
Background: Interstitial Lung Diseases is a group of disorders where the pulmonary interstitium, alveolar structures and the small airways are affected. Identification of a specific pattern on HRCT, with a thorough clinical evaluation can help a physician in narrowing down the differential diagnosis for the underlying cause. Usual Interstitial Pneumonia (UIP) is a frequently identified pattern. Differentiating patients with definite UIP pattern, into IPF and non-IPF spectrums is important. Aim of this study is to compare UIP patients with a secondary cause vs Idiopathic Pulmonary Fibrosis. Methods: Statistically 33 patients having UIP pattern on HRCT were evaluated based on the history of extrapulmonary symptoms, environmental exposure, drugs and subsequent serology testing. Patients were divided into two groups - IPF and UIP with a secondary cause. Both groups were compared on various clinical parameters. Inferences were drawn from the same. Results: Total 66.6% patients were identified to have Idiopathic Pulmonary Fibrosis, 33.3% had UIP with a secondary cause. Majority of patients with a secondary cause had Connective Tissue Disorder (90.9%) and one patient of Chronic Hypersensitivity Pneumonitis (HP). Conclusions: Absence of extrapulmonary symptoms in UIP patients need no further investigations and can be diagnosed as a case of IPF. However, presence of extrapulmonary symptoms needs further evaluation to diagnose the underlying disease and start treatment for the same.